Nonrelativistic plasma HF-electronics - Onishchenko, I.N. (Вопросы атомной науки и техники, 2005)
The main physical principles for the elaboration of plasma and hybrid plasma-filled microwave devices based on the beam-plasma interaction are formulated. The theoretical and experimental results of the investigations of electromagnetic oscillations excitation in beam-plasma systems carried out in National Science Center “Kharkov Institute of Physics and Technology” are presented. The electrodynamics of plasma-filled slow wave structures, nonlinear stage of beam-structure interaction, and stochastization mechanism are studied. Some experimental installations elaborated are described and obtained results on power level, efficiency, and spectra аre shown. Сформульовані основні принципи розробки плазмових і гібридних плазмонаповнених СВЧ-приладів, заснованих на пучково-плазмовій взаємодії. Представлені результати теоретичних і експериментальних досліджень збудження електромагнітних коливань в пучково-плазмових системах, які проводились в ННЦ ХФТІ. Досліджені електродинаміка плазмонаповнених уповільнюючих структур, нелінійна стадія взаимодії з ними пучків і механізми стохастизації. Описані деякі експериментальні стенди і приведені отримані на них потужність, ккд і спектри. Сформулированы основные принципы разработки плазменных и гибридных плазмонаполненных СВЧ- приборов, основанных на пучково-плазменном взаимодействии. Представлены результаты теоретических и экспериментальных исследований возбуждения электромагнитных колебаний в пучково-плазменных системах, которые проводились в ННЦ ХФТИ. Исследованы электродинамика плазмонаполненных замедляющих структур, нелинейная стадия взаимодействия с ними пучков и механизмы стохастизации. Описаны некоторые экспериментальные стенды и приведены полученные на них мощность, кпд и спектры.